Monsters university ([s.l] : Disney, 2013)
Ever since college-bound Mike Wazowski was a little monster, he has dreamed of becoming a Scarer - and he knows better than anyone that the best Scarers come from the Monster Universtiy (MU). But during his first semesterat MU, Mike's plans are derailed when he crosses paths with hotsot James P. Sullivan, "Sulley", a natural-born Scarer. The pair's out-of-control competitive spirit gets them both kicked out of the University's elite Scare Program. With their dreams temporarily dashed, they realize they will have to work together, along with an odd bunch of misfit monsters, if they ever hope to make things right.